Developmental sentence scoring of a five year old girl - Girija Nagaraja (Journal of All India Institute of Speech and Hearing)
Transcribed tape recordings of the spontaneous speech of a five year old girl have been scored according to Laura Lee and Susan Canters’ Developmental Sentence Scoring (DSS) technique. Enyde’s DSS score was compared with others of her age group in Laura Lee and Susan Canters’ study